(untitled) (Media Kesehatan Masyarakat Indonesia, 2025)
Providing breast milk to babies becomes one of the keys to growth and development. Breast milk contains various crucial nutrients needed for the growth and development period of babies. To analyze the effect of consuming local vegetables containing galactagogues on breastfeeding intensity. This study was a cross-sectional study conducted at 38 Community Health Centers in Tasikmalaya Regency in 2024. The population was 5971 people. The sampling technique is proportional sampling. The study sample was 450 breastfeeding mothers. The independent variables were consumption behaviros of galactagogue vegetables, such as katuk leaves, moringa, spinach, young papaya, and banana blossoms. The dependent variable was breastfeeding intensity measured by the frequency and duration of breastfeeding. Bivariate analysis used chi-square and multivariate analysis used multiple logistic regression. The results of the study showed that consumption of katuk leaves and banana flowers would increase the frequency of breastfeeding (aOR: 0.40; p value=0.000; 95%CI: 0.23 - 0.61 and aOR: 2.23; p value=0.004; 95%CI: 1.30 - 3.85) and extend the duration of breastfeeding (aOR: 3.67; p value=0.000; 95%CI: 1.99 - 6.77 and aOR: 3.01; p value = 0.026; 95%CI: 1.14 - 7.98). Breastfeeding mothers can consume local foods made from processed banana blossoms and katuk leaves in an effort to increase breast milk production by utilizing local foods.